Introduction to Knowledge Management. - Emerald Group Publishing (Emerald Group Publishing, 2005)
At the centre of every successful organization is the knowledge of key managers and their ability to apply it. In a globally competitive world, it is becoming increasingly important to capture knowledge, develop people and establish lifelong learning to continue to compete at the leading edge of business. By definition, managing knowledge is not what "knowledge management" is about. It is about exploiting and realizing knowledge in the workforce, fostering a culture where knowledge sharing can thrive and how an organization develops its people and their knowledge as individuals, as teams and at an organizational level. Knowledge relies not on technology but on people, who have knowledge, develop it and act on the basis of it. Knowledge is likely to play a big part in corporate culture in the new millennium. To quote the head of knowledge management at Unilever, David Smith, "Knowledge management is the only long-term, sustainable source of competitive advantage." Knowledge management expert Paul Quintas believes that many mistakes have been made and will continue to be made in KM initiatives until organizations fully understand what KM can do for them. For example, one of the most famous of these mistakes is to concentrate entirely on the knowledge individuals and the organization already has. Whilst tapping into knowledge assets is of course very important, it is also equally important to create a new knowledge environment. At a basic level, Quintas believes that KM is about putting knowledge "centre stage" in all business and organizational processes. A potential stumbling block here is to be ignorant of the fact that all processes that deliver value to a business have a "knowledge dimension." Therefore an organization must realize the central role that the fostering, collection and dissemination of knowledge must play if a KM initiative is to succeed. The real challenge in knowledge management is to create a business environment in which knowledge can be aggregated and applied on a continuous basis. According to Paul Quintas, this will involve creating a business culture in which employees are given time and recognition for knowledge sharing.